2010
DOI: 10.1007/s11064-010-0346-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Disorder. A Biological and Clinical Overview

Abstract: Although vascular dementia (VaD) represents the second most common cause of dementia after Alzheimer's disease (AD) in the elderly, and is referred as the "silent epidemic of the twenty-first century", there is still a controversy on terminology, classification and diagnostic criteria of VaD. The diagnosis of VaD resides in clinical criteria determining a cognitive impairment, the presence of cerebrovascular disease and, only in the case of post-stroke dementia or multi-infarct dementia, a temporal relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 31 publications
(26 reference statements)
0
45
0
1
Order By: Relevance
“…1 It is reported that about 20% of dementia cases are diagnosed as VaD around the world. 2 Permanent occlusion of bilateral carotid arteries had been wildly used for the VaD model because of chronic cerebral hypoperfusion (CCH).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is reported that about 20% of dementia cases are diagnosed as VaD around the world. 2 Permanent occlusion of bilateral carotid arteries had been wildly used for the VaD model because of chronic cerebral hypoperfusion (CCH).…”
Section: Introductionmentioning
confidence: 99%
“…potential biomarkers to correlate with the pathogenesis of VaD. However, further studies are needed to establish their clinical significance 47,60. The proposed biomarker genes predisposing to cerebrovascular disease are ACE, AGT, eNOS, PON, MTHFR, MEF2A, ALOX5, LTA, APOM, and PDE4D.…”
mentioning
confidence: 99%
“…Unfortunately, up to date there are no resolute clinical criteria for VCI, still the common clinical finding is progressive gait alteration and incontinence. (Battistin & Cagnin, 2010) And recently, there is a growing interest in the clinical and scientific area involving the elderly community in investigation of elderly fallers. Interestingly, recurrent fallers had lower MMSE scores than single fallers or non-fallers.…”
Section: Vascular Cognitive Impairmentmentioning
confidence: 99%